052 Evaluation of a mental health and psychological wellbeing drop-in centre in a paediatric hospital setting. (December 2018) - Catanzano, M; Souray, R; Tibber, M; Kothari, R; Bennett, S; Liang, H; Heyman, I; Shafran, R
Abstract : Background: Young people with a physical illness are at significantly greater risk of developing emotional and behavioural difficulties. Such problems may also have negative consequences on the management and course of the physical illness itself. This study was part of a broader project to examine the acceptability, feasibility and impact of a Mental Health and Psychological Wellbeing Drop-in Centre in a hospital setting. The aims of this particular pilot investigation were: (i) to establish whether there is a need for such a resource amongst the hospital's patient population, (ii) to characterise the nature and severity of symptoms amongst patients presenting to the centre, and (iii) to establish the types of support that are requested and/or most needed. Methods: A drop-in 'booth' located in the reception of Great Ormond Street Hospital (GOSH) was run by clinicians and researchers over the course of one week (Monday to Saturday), serving as a focus for recruitment and space for treatment, with a Clinical Psychologist or Psychiatrist on-call throughout. Basic demographic data were gathered and symptom severity measured using standardised emotional and behavioural difficulties questionnaires (SDQ, GAD-7 and PHQ-9). Results: 31 participants were recruited from 28 families. The median age of young people presenting was 9 years (IQR: 6.5–11); 47% identified as White British and 55% were male. Primary problems identified included: anxiety (45%), challenging behaviour (31%) and low mood (21%). Whilst 75% of young people recruited were in the clinical range with respect to scores on the SDQ, 50% and 30% of parents scored in the clinical range for anxiety and depression, respectively. 32% of families reported never having received mental health input for their child. Conclusion: A considerable proportion of patients and family members attending GOSH met the clinical threshold for common mental health problems, indicating a potential, as yet unmet, need.